ISOLATION OF PROTEASE ENZYME FROM CHAYOTE FRUIT (Sechium edule (Jacq.) Sw.) WITH AMMONIUM SULFATE FRACTINATION METHOD - Ratnayani, Ketut; Kusumaningrum, Lia (International Journal of Biosciences and Biotechnology; Vol 2 No 2 (2015), 2016)
Protease is an enzyme that is capable to hydrolyze (breakdown) protein molecules intosimpler compounds such as small peptides and amino acids. The aim of the research was toisolate protease enzyme from chayote (Sechium edule (Jacq.) Sw.) using fractinationammonium sulfate method and to find out the optimum saturation level of the ammoniumsulfate. P rotease activity examination of each fraction of ammonium sulfate was performedusing Anson method. Protein content assay was determined using Biuret method. The resultsshowed that crude extract protease of chayote had specific activity of 3,7338 x 10-3 U/mg. Theoptimal saturation levels of ammonium sulfate for protease chayote precipitation was 40-50%. At this saturation level, the highest enzyme spesific activity were 16,00 x 10-3 U/mg,with four times purifying of protease enzyme from the crude extract protease.
Keywords: protease; protease activity; ammonium sulfate; specific activity